Research on the Strength Variation of Root-Clay Systems under Freeze-Thaw Action - Lin Yang; Hengxing Wang; Chunpeng Han; Hong Guo; Yafeng Gong; Yulong He (Advances in Materials Science and Engineering, 2017)
The aim of this paper is to study the influence of an effective root system of rhizome plants on the reinforcement of slope soil under freeze-thaw conditions. This study focused on the mechanical properties between roots and clay in the root system of four plant species from different regions of China (northeast, northern, central, and southern areas): Setaria viridis, Eleusine indica, Zoysia japonica, and Carex leucochlora. Based on the interfacial friction effects between the plant roots and the soil, pull-out tests and unconfined compressive strength tests were conducted on the reinforced soil system for varying numbers of freeze-thaw cycles. Several stages of the pull-out process of the root system in clay are explicitly proposed based on the interfacial friction test results. The results showed that the friction effect between Zoysia japonica roots and the soil was the most significant and that these roots had the best reinforcement effect. In contrast, the friction and reinforcement effects between Setaria viridis roots and the soil were the worst, and the resulting unconfined compressive strength was the smallest. However, the freeze-thaw resistance ability of the Setaria viridis and soil system was stronger than that of the Zoysia japonica system.